Collaborating with ChatGPT in argumentative writing classrooms - Su, Yanfang; Lin, Yun; Lai, Chun (Assessing writing, 2023)
Composing high-quality argumentative writing requires consideration of the dialogical, structural, and linguistic aspects of argumentation. However, finding an ideal peer student to practice argumentation skills can be challenging, and providing feedback on lower-level language concerns and complex issues related to content and organization can be time-consuming for teachers. In this article, we suggest the integration of ChatGPT, a chatbot released by OpenAI in 2022, into argumentative writing classrooms as a promising solution. The article explores the possibilities of ChatGPT in assisting students with tasks such as outline preparation, content revision, proofreading, and post-writing reflection. We also acknowledge the limitations of ChatGPT and offer suggestions for future considerations in teaching and research. •Collaboration with ChatGPT in argumentative writing classrooms.•Using ChatGPT as a writing evaluator that provides feedback.•Using ChatGPT as a virtual peer engaged in conversations around writing topics.•Integration of ChatGPT to support pre-writing, during-writing and post-writing.